Natural gas purification and olefin/paraffin separation using thermal cross-linkable co-polyimide/ZIF-8 mixed matrix membranes - Askari, Mohammad; Chung, Tai-Shung (Journal of membrane science, 2013)
Using three 6FDA-based polyimides (6FDA-Durene, 6FDA-Durene/DABA (9/1), 6FDA-Durene/DABA (7/3)) and nano-size zeolitic imidazolate framework-8 (ZIF-8), we have fabricated mixed matrix membranes (MMMs) with uniform morphology comprising ZIF-8as high as 40wt% loading by directly mixing as-synthesized ZIF-8 suspension into the polymer solution. Permeability of all gases (CO2, CH4, C3H6, and C3H8) increases rapidly with an increase in ZIF-8 loading. However, the addition of ZIF-8 nano-particles into the polymer matrix increases the ideal CO2/CH4 selectivity of only 6.87%, while the ideal C3H6/C3H8 selectivity improves 134% from 11.68 to 27.38 for the MMM made of 6FDA-Durene/DABA (9/1) and 40wt% ZIF-8. Experimental data show that the plasticization resistance and gas pair selectivity of MMMs are strongly dependent on the amount of cross-linkable moiety and annealing temperature. MMMs made of 6FDA-Durene do not show considerable improvements on resistance against CO2-induced plasticization after annealing at 200–400°C, while MMMs synthesized from cross-linkable co-polyimides (6FDA-Durene/DABA (9/1) and 6FDA-Durene/DABA (7/3)) show significant enhancements in CO2/CH4 and C3H6/C3H8 selectivity as well as plasticization suppression characteristics up to a CO2 pressure of 30atm after annealing at 400°C due to the cross-linking reaction of the carboxyl acid (COOH) in the DABA moiety. The MMM made of 6FDA-Durene/DABA (9/1) and 40wt% ZIF-8 possess a notable ideal C3H6/C3H8 selectivity of 27.38 and a remarkable C3H6 permeability of 47.3 Barrer. After thermally annealed at 400°C, the MMM made of 6FDA-Durene/DABA (9/1) and 20wt% ZIF-8 shows a CO2/CH4 selectivity of 19.61 and an impressive CO2 permeability 728 Barrer in mixed gas tests. The newly developed MMMs may have great potential for industrial nature gas purification and C3H6/C3H8 separation. [Display omitted] •Cross-linkable co-polyimide/ZIF-8 mixed matrix membranes (MMMs) are fabricated.•Effects of diamine ratio on polymer structure and gas separation performance are studied.•Effect of heat treatment temperature on MMM performance is investigated.•Increasing ZIF-8 loading leads to increase MMM permeability for all gasses.•Cross-linkable co-polyimides thermally treated at 400°C have shown selectivity enhancement.